1989
DOI: 10.1099/0022-1317-70-12-3261
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction for Human Picornaviruses

Abstract: SUMMARYWe have used enzymic amplification of specific nucleic acid sequences followed by hybridization, for the rapid detection and typing of human picornaviruses after cell culture isolation. The test is based on the synthesis of cDNA, the polymerase chain reaction and the use of oligonucleotide probes. The primers were selected from the 5' non-coding region of the genome representing highly conserved regions. Sequences specific to enteroviruses and rhinoviruses were used as probes. The assay was able to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
131
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(138 citation statements)
references
References 16 publications
5
131
0
2
Order By: Relevance
“…Hyypiä et al (9) also reported this abnormality. The binding energy of these probes was found to be higher than that deduced from linear sequence analysis.…”
mentioning
confidence: 83%
“…Hyypiä et al (9) also reported this abnormality. The binding energy of these probes was found to be higher than that deduced from linear sequence analysis.…”
mentioning
confidence: 83%
“…Respiratory syncytial virus, adenovirus, influenza A and B, and parainfluenza types 1, 2, or 3 were either detected by 1) direct fluorescent Ab testing with virus-specific mAbs (Meridian Bioscience and Dako) or 2) isolation in cell culture (cell lines include LLC-MK, A549, Hep-2, Vero, and MRC-5) and identification with the virus-specific monoclonal antisera, 48 h after inoculation. Human rhinovirus (19,20) and coronavirus 229E and OC43 (21) were detected by previously described RT-PCRs, and human metapneumovirus detection utilized in-house primers designed to target nuc and matrix genes. For aspirates with sufficient sample remaining for retesting (the majority), respiratory viruses were detected by Respiratory MultiCode-PLx assay (22) and human rhinovirus was identified with a molecular typing assay (23).…”
Section: Subjects and Clinical Assessmentsmentioning
confidence: 99%
“…Therefore, PCR is the preferred method for detection of viruses in this material (Espy et al, 2006;Read et al, 1997;Romero 1999;Rotbart HA & Romero JR, 1995;van Doornum et al, 2007). But while with cell culture, both EVs and HPeVs can be diagnosed, PCR specific for EVs will fail to detect HPeVs because the targeted 5'UTR is too diverse between HPeVs and EVs (Beld et al, 2004;Benschop et al, 2006a;Hyypia, 1989;Hyypia et al, 1989;Oberste et al, 1999). Therefore a separate RT-PCR specifically targeting the 5'UTR of HPeVs is required.…”
Section: Laboratory Findings and Diagnosis Of Hpev Infectionmentioning
confidence: 99%